Hubungan Work Family Conflict dengan Marital Satisfaction pada Guru Sekolah Dasar di Kota Bandung - Rahayu Auliya Prasisti; Anna Rozana (UNISBA Press, 2022)
Abstract. During COVID-19 pandemic, make teachers must be able to share their roles as teachers at school and home at the same time. When one of the roles can’t be fulfilled properly, work family conflict occur. Work family conflict raise negative impact to teachers wellbeing, which can make aspect of marital satisfaction not fulfilled properly. The result, negative feeling will appear, not only for mother but also for her husband, child, and family. So, the purpose of this study was to determine the relationship between work family conflict and marital satisfaction for elementary school teachers in Bandung city. This research uses a quantitative approach with a correlational research design. The measuring instrument used is work family conflict scale from Carlson, Kacmar, & Williams which had adapted by Indah Soca Kuntari, M.Psi., Psikolog and ENRICH Marital Satisfaction Scale from Fower & Olson which had adapted by Maya Khairani, S..Psi., M.Psi. This research was conducted on 106 elementary school teachers in Bandung city predetermined criteria. The data analytical technique for this research is rank spearman correlation and the results showed that there is a negative relationship between the two variables with correlation coefficient of -0,420. Abstrak. Di masa pandemi COVID-19 seperti ini, membuat guru harus dapat membagi perannya sebagai guru di sekolah dan di rumah dalam waktu bersamaan. Ketika salah satu peran tidak terpenuhi, maka terjadilah work family conflict. Work family conflict ini berdampak negatif pada kesejahteraan guru yang dapat membuat aspek dalam marital satisfaction tidak terpenuhi dengan semestinya. Akibatnya, akan muncul perasaan negatif tidak hanya kepada ibu tetapi juga pada suami, anak, dan keluarganya. Sehingga tujuan dari penelitian ini adalah untuk mengetahui hubungan antara work-family conflict dengan marital satisfaction pada guru Sekolah Dasar di Kota Bandung. Penelitian ini menggunakan pendekatan kuantitatif dengan desain penelitian korelasional. Alat ukur yang digunakan yaitu Work Family Conflict Scale dari Carlson, Kacmar & Williams yang telah diadaptasi oleh Indah Soca Kuntari, M.Psi., Psikolog dan ENRICH Marital Satisfaction Scale dari Fower & Olson yang telah diadaptasi oleh Maya Khairani, S..Psi., M.Psi., Psikolog. Penelitian ini dilakukan pada 106 guru sekolah dasar di Kota Bandung yang kritertianya sudah ditentukan. Analisis data yang digunakan yaitu rank spearman correlation dan hasilnya menunjukkan bahwa terdapat hubungan negatif antara kedua variabel dengan correlation coefficient sebesar -0,420